Paepalanthus uai (Eriocaulaceae), a new name for the later homonym Paepalanthus petraeus Echtern. & Trovó - Andrino, Caroline Oliveira; Costa, Fabiane Nepomuceno; Sauthier, Luana Jacinta; Sano, Paulo Takeo (Phytotaxa, 2021)
N/A